2024
DOI: 10.1002/cam4.6935
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of peripheral blood neutrophil extracellular traps in the diagnosis and progression of malignant tumors

Min Wang,
Xiaoyan Lv,
Ying Wang
et al.

Abstract: Background and AimsThe mortality rate associated with malignant tumors remains high and there is a lack of effective diagnostic and tumor progression markers. Neutrophil extracellular traps (NETs) can promote tumor‐associated thrombosis, invasive metastasis, and inflammatory responses, but there is a lack of research on the value of measuring NETs in the peripheral blood of patients with malignancies.MethodsWe included 263 patients with malignancies (55 gliomas, 101 ovarian, 64 colorectal, and 43 lung cancers)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Moreover, recent studies have reported that serum levels of H3Cit, as well as circulating MPO–DNA or NE–DNA complexes, are associated with the diagnosis and/or progression of multiple cancers with much more specificity. 51 , 78 , 136 , 148 , 167 , 179 , 180 , 184 , 188 , 191 , 194 These markers differentiate NETs from other types of nontumor‐derived cfDNA, which increases the likelihood of therapeutic translation. MPO–DNA or H3Cit has been employed in clinical trials as NETs biomarkers and prognostic indicators to evaluate the risk of thrombosis in patients with cancer including myeloproliferative neoplasms, pancreatic, gastric, 182 and colorectal cancer.…”
Section: Clinical Utility Of Nets As a Cancer Biomarkermentioning
confidence: 99%
“…Moreover, recent studies have reported that serum levels of H3Cit, as well as circulating MPO–DNA or NE–DNA complexes, are associated with the diagnosis and/or progression of multiple cancers with much more specificity. 51 , 78 , 136 , 148 , 167 , 179 , 180 , 184 , 188 , 191 , 194 These markers differentiate NETs from other types of nontumor‐derived cfDNA, which increases the likelihood of therapeutic translation. MPO–DNA or H3Cit has been employed in clinical trials as NETs biomarkers and prognostic indicators to evaluate the risk of thrombosis in patients with cancer including myeloproliferative neoplasms, pancreatic, gastric, 182 and colorectal cancer.…”
Section: Clinical Utility Of Nets As a Cancer Biomarkermentioning
confidence: 99%